A new cunaxid genus with descriptions of two new species from Brazil (Acari: Prostigmata: Bdelloidea: Cunaxidae) - Den Heyer, Jacob; De Castro, Tatiane Marie Martins Gomes [UNESP] (My University, 2008)
The genus Pseudobonzia Smiley 1975 is revised and divided into two genera. The genus Pseudobonzia Smiley, 1975, with its type species and five other related species, is retained. The remainder of the group is now known as Coleobonzia gen. nov. of which the main characteristics are provided. Coleobonzia argillae (Den Heyer, 1977) is designated as type species for the new genus. Two species from Brazil, viz. Coleobonzia clava sp. nov. and C. moraesi sp. nov. are described and figured. A key to the two genera as well as a key to the Brazilian and South African species of the new genus are provided. Copyright © 2008 Magnolia Press.
Keywords: Coleobonzia; Identification key; New species; Pseudobonzia; Taxonomy; Acari; Bdelloidea (mites); Clava; Prostigmata